IDENTIFYING SPATIAL PATTERNS OF A TYPE 38 HOUSE WITH AN ISLAMIC ARCHITECTURE APPROACH (CASE STUDY: MASDA 1 HOUSING COMPLEX) - Samsudin Raidi; Nur Jannatu Assholikhah (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
A home is where humans engage in family interactions; naturally, humans are social beings who require assistance from others. In Islamic teachings, we are instructed to apply Islamic values, one of which is